2015
DOI: 10.1371/journal.pone.0132746
|View full text |Cite
|
Sign up to set email alerts
|

HIF-1α Induces Multidrug Resistance in Gastric Cancer Cells by Inducing MiR-27a

Abstract: This study aimed to determine the correlation between HIF-1α and miR-27a expression and to evaluate the effect of inhibition of HIF-1α expression on miR-27a expression and drug resistance in gastric cancer (GC). In the present study, real time-PCR and Western blot were performed to detect the expression of HIF-1α in GC tissues and cell lines. Then, OCUM-2MD3/L-OHP cells were transfected with HIF-1α-siRNA, a miR-27a mimic or pcDNA-HIF-1α, and cell survival was determined via the MTT assay. The expression of HIF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
42
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 33 publications
3
42
0
Order By: Relevance
“…Both of these could account for the increase seen at both the transcriptional and resultant protein level. A variety of micro RNAs which are regulated by HIF-1α have been shown to inhibit IL-10 production; these include miR-27a and Let-7 family members Let-7b, Let-7c, and Let-7f (8589). While few studies have focused on the role of HIF-1α in controlling mRNA stability, it binds to VEGF mRNA and regulates transcript decay (90, 91).…”
Section: Discussionmentioning
confidence: 99%
“…Both of these could account for the increase seen at both the transcriptional and resultant protein level. A variety of micro RNAs which are regulated by HIF-1α have been shown to inhibit IL-10 production; these include miR-27a and Let-7 family members Let-7b, Let-7c, and Let-7f (8589). While few studies have focused on the role of HIF-1α in controlling mRNA stability, it binds to VEGF mRNA and regulates transcript decay (90, 91).…”
Section: Discussionmentioning
confidence: 99%
“…Zhao and co-workers recently reported that HIF1alpha suppresses MDR1/P-glycoprotein in gastric cancer by inhibiting miR-27a expression in gastric cancer [62], and in colon cancer cells, inhibition of HIF1 leads to downregulation of p -glycoprotein and reversal of multidrug resistant phenotype [63]. In contrast, pronounced hypoxia has minor effect on p -glycoprotein expression and activity [64], while acidosis, a feature of the hpoxic micro-environement, increases p -glycoprotein activity [65].…”
Section: Methodsmentioning
confidence: 99%
“…MiR‐20b, miR‐27a, and miR‐181a have been shown to enhance the resistance of GC cells to EOX through targeting HIF1A/HIF‐1α, MDR1, and HIPK2 . The miR‐27a was another oncogene that could regulate HIF‐1α which is closely related to MDR in GC and may also inhibits LRP, Bcl‐2, and MDR1/P‐gp . Zhang et al reveal that miR‐107 was downregulated in MDR GC cell lines and elevated the sensitivity of GC cells to DOX by inhibiting drug efflux and suppressing P‐gp expression.…”
Section: Mirnas and Drug Resistance In Gcmentioning
confidence: 99%